Peat stabilization with carbide lime - Said, J.M.; Razali, I. (Universiti Malaysia Sarawak (UNIMAS), 2009)
This paper presents a research on peat stabilization with objectives that are to improve the soil to be more stable and to have higher strength and to find a cheap alternative material that can be used ad stabilizing agent. In this research, an admixture, which is carbide lime, a by product of acetylene is used to stabilize the peat soil. Laboratory tests on physical properties and shear strength are done. The research is done on peat soil that is collected from Matang area in Kuching, Sarawak.